Population dynamics of larval stages of Tauriphila risi Martin and Erythemis attala (Selys) in Punta Lara gallery forest, Buenos Aires, Argentina (Anisoptera: Libellulidae) - Rodrigues Capítulo, Alberto (2000)
Laral populations of the 2 species were studied in a lentic freshwater environment. 13 larval instars were recognized from plots of head width and length of wig-pads.Density, populations dynamics, age, structure, flying period and winter quiescence were analysed. Both uni- and semivoltine individuals were found. Microhabitat differences were found beteen the 2 spp, T. risi preferring Pistia stratiotes and Hydrocotyle ranunculoides, whereas E. attala preferred lemnaceas.  A life table was constructed  for T. risi, which showed mortality rate maxima at hatching and at 10 and 23 months.